ACCOUNTING ADMINISTRATION OF UNEMPLOYMENT INSURANCE. - Larimore, T. R. (The Accounting Review, 1945)
The article presents information on accounting administration of unemployment insurance. The social security act does not prescribe the type of administration that any state should establish; however, certain minimum requirements had to be fulfilled before the Board would approve a state law. This leeway in the Federal law allowed each state an opportunity to select an administrative agency in harmony with its peculiar needs, fitted into the composition of the state government and the demands of local public opinion and adapted to the plan of administering other state labor laws. A review of the essential functions indicates clearly the heavy burden resting upon the administrative units for the successful carrying out of the purposes of unemployment compensation legislation. One of the early functions is the establishment and maintenance of an adequate public relations and information service. Interpretation and clarification of the state law becomes an important task of the administrative agency. Office management, planning and supervision of the budget are also duties of administration. Forms must be drafted; reporting procedures must be determined; accounting equipment and records must be selected and proper routines for the collection, recording and processing of information must be established.